(untitled) (Journal of Health, Population and Nutrition, 2011)
High-energy diet and sedentary lifestyle fail to completely explain the epidemic of obesity in developing countries. In this cross-sectional survey, the prevalence and patterns of overweight/obesity were assessed among women in a slum in Brazil. Using anthropometric measurements, shorter form of the International Physical Activity Questionnaire (IPAQ), and a 24-hour diet recall questionnaire, data were collected from 632 women aged 20-60 years. The prevalence of overweight and obesity was 29% and 17% respectively. Physical inactivity was found in 17% of the women; 12% of them had short stature, and 44% had energy intake below the recommended dietary allowance. Results of multiple logistic regression showed that overweight/ obesity differed significantly (p<0.05) in the following aspects: abdominal circumference, energy intake, and short stature. A high prevalence of overweight/obesity was found in a very poor community associated with high-energy intake and short stature. Key words: Caloric intake; Cross-sectional studies; Obesity; Physical activity; Slum; Brazil DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7876 J HEALTH POPUL NUTR 2011 Jun;29(3):286-289